Pengaruh Profil Pemimpin, Komitmen Pemimpin, Dan Penggunaan Kekuasaan Terhadap Kinerja Pegawai (Studi pada Yayasan Tarbiyah Islam Nguling Kab. Pasuruan) - Muh. Dhiyaurrohman; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis research aims to find out and analyze the influence of leader profiles, leader commitments and the use of power on employee performance in Yasyasan Tarbiyah islam kab. Pasuruan.. In this study the data collection method used a questionnaire method (questionnaire). The type of data used in this study is primary data. The method of analysis used in this research is multiple linear regression. This study uses data from a questionnaire distributed to to employees of the Tarbiyah Islam Foundation Kab.Pasuruan and the sample is taken using non-probability sampling. The number of samples taken was 41 respondentsThe results showed that the profile and use of power had no effect on employee performance. While the commitment of leaders affects the performance of employeesKeywords: leader profiles, leader commitments, the use of power, employee performance.